2017
DOI: 10.1007/s40264-017-0553-y
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Safety of Anti-VEGF Drugs: Analysis of the Italian Spontaneous Reporting System

Abstract: This study documented that serious ADRs and systemic toxicity may occur not only with systemic use of anti-VEGF drugs in patients with cancer but also with intravitreal administration. Close monitoring of cardio/cerebrovascular adverse events should be considered during treatment with all anti-VEGF drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Specifically, ranibizumab binds to the VEGF-A, one of the five isoforms of the VEGF family and one of the strongest inducers of vascular permeability ( Yla-Herttuala et al, 2007 ), which showed neuroprotective effects in several in vitro and in vivo PD models ( Silverman et al, 1999 ; Pitzer et al, 2003 ; Yasuhara et al, 2004 ; Tian et al, 2007 ; Yue et al, 2014 ). A recent study on the Italian ADR Spontaneous Reporting System showed 3 reports of “extrapyramidal syndrome” due to intravitreal bevacizumab and 1 to intravitreal aflibercept ( Cutroneo et al, 2017 ). Similarly, in the Food and Drug Administration’s Adverse Event Reporting System, three cases of neurodegenerative disorders have been reported following bevacizumab use ( Shamloo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ranibizumab binds to the VEGF-A, one of the five isoforms of the VEGF family and one of the strongest inducers of vascular permeability ( Yla-Herttuala et al, 2007 ), which showed neuroprotective effects in several in vitro and in vivo PD models ( Silverman et al, 1999 ; Pitzer et al, 2003 ; Yasuhara et al, 2004 ; Tian et al, 2007 ; Yue et al, 2014 ). A recent study on the Italian ADR Spontaneous Reporting System showed 3 reports of “extrapyramidal syndrome” due to intravitreal bevacizumab and 1 to intravitreal aflibercept ( Cutroneo et al, 2017 ). Similarly, in the Food and Drug Administration’s Adverse Event Reporting System, three cases of neurodegenerative disorders have been reported following bevacizumab use ( Shamloo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The many limitations of RCTs in capturing ADRs (Sultana et al, 2013) highlight the importance of confirming such safety issues using real-world studies. An Italian nationwide pharmacovigilance study confirmed the plausibility of intravitreal anti-VEGF drugs being associated with systemic ADRs, including arterial thromboembolic events, such as stroke and myocardial infarction (Cutroneo et al, 2017). In addition to these ADRs, it has recently come to light that anti-VEGF drugs could be a risk factor for neurodegenerative processes.…”
Section: Introductionmentioning
confidence: 95%
“…However, TRPC1 gene knockout in zebrafish and mice showed the opposite results [7,8], which proved that TRPC expression and effect were different in different tissues of different species and genera. Although current antivascular endothelial growth factor (VEGF) drugs cause clinically visible regression of new blood vessels, there is evidence that they can increase the occurrence of retinal traction detachment and other adverse reactions in the treatment of PDR and choroidal neovascularization [9,10]. The specific role of the TRPC family in endothelial cell formation in retinal neovascularization has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%